Specific cutaneous infiltrates in patients with haematological neoplasms: a retrospective study with 49 patients. (5th January 2021) - Calado, Rebeca; Relvas, Maria; Morgado, Francisca; Cardoso, José Carlos; Tellechea, Oscar
Abstract: Background: Haematological neoplasms account for around 9% of all cancers, and they are recognised as an important cause of skin infiltration. However, studies analysing cutaneous metastasis of haematological neoplasms are scarce. We describe the clinical spectrum and outcomes of specific cutaneous manifestations of leukaemias, lymphomas, multiple myeloma (MM), and blastic plasmacytoid dendritic cell neoplasm (BPDN) and make a review of the literature. Methods: Data from 49 patients diagnosed with secondary cutaneous infiltration of systemic haematological neoplasms over the last 10 years in a tertiary dermatology centre were retrospectively collected, and clinical‐evolutive features were analysed. Results: Most cases were lymphoma (44.9%, n = 22), followed by leukaemia cutis (38.8%, n = 19), secondary plasmacytoma (10.2%, n = 5) and BPDN (6.1%, n = 3). Nodules were the predominant type of lesion, and most patients presented with multiple (≥3) lesions. In 51% ( n = 25) of cases, cutaneous infiltration was detected before the diagnosis of the underlying malignancy. The patients in diverse nosological groups did not differ in terms of survival ( P = 0.052). Conclusions: We recognise the clinical heterogeneity of specific cutaneous infiltrates. The high proportion of cases in which skin involvement was key to the diagnosis of systemic malignancy emphasises the role of the dermatologist in recognising and correctly managing these patients.